Concept of myocardial fatigue in reversible severe left ventricular systolic dysfunction from afterload mismatch: a case series. Issue 3 (7th March 2021) - Tran, Patrick; Joshi, Mithilesh; Banerjee, Prithwish
Abstract: Background : There is already extensive literature on the natural history of hypertensive heart disease (HHD) and aortic stenosis (AS). Once these patients develop severe left ventricular systolic dysfunction (LVSD) despite guideline-directed therapy for heart failure (HF), it is often thought to be end-stage from irreversible adverse remodelling. Our case series challenges this traditional paradigm. A more holistic model that factors in the interactions between the ventricle and vasculature is required. Based on a novel hypothetical concept of myocardial fatigue, we propose that occasionally LVSD is not an inherent myocardial or valvular disease but a consequence of an arterial afterload mismatch. By addressing this, the ventricle may recover and contract efficiently in unison with the arterial system. Case summary : We present two cases of severe LVSD in a young lady with long-standing essential hypertension and a gentleman with stable severe AS. Both patients were already established on HF medications. After optimizing their blood pressure control, repeat echocardiography revealed normalization of left ventricular ejection fraction within 3 months, along with a demonstrable improvement in ventricular–arterial coupling and for AS, a reduction in valvular-arterial impedance. Discussion : Just as Frank–Starling's law was discovered by initially drawing analogies to skeletal muscle behaviour, it is biologically plausible that cardiac fatigue can occur in the setting of afterload mismatch. The chance of recovery rests upon early recognition before it transitions to irreversible myocardial damage. Only by testing new emerging theories of HF can we galvanize original research and find new avenues to understanding this complex syndrome.